Analysis of heterogeneous tests for sheet metal mechanical behavior - Oliveira, Miguel Guimarães (2020)
Strategies combining heterogeneous mechanical tests and full-field strain measurement techniques are providing increasingly more valuable data, ensuring calibrated constitutive models for the accurate representation of the elastoplastic behavior of sheet metals. However, the accuracy of these strategies is still dependent on many factors, such as the shape of the specimen, the choice of an appropriate strain field measurement technique, or the selection of an identification strategy. Recently, many heterogeneous tests with different specimen shapes and boundary conditions have been proposed using optimization techniques or empirical knowledge. Examples of these specimens include shapes based on cubic splines, notches, holes, slits or even Greek letters. However, the qualitative and quantitative comparison of each heterogeneous test is a difficult task, as studies tend to use different materials and representations of the strain and stress tensors. As a result, the selection of a single heterogeneous test is still a dilemma and a subject under research. Thereby a set of indicators to evaluate and qualitatively rank each heterogeneous test is proposed, calculated through the strain and stress fields on the sheet plane of the specimen, within a virtual (numerical) approach, and investigate its application to steel and aluminum, to account for the material dependency.